The Influence of Brand Trust, Brand Awareness, Discount and Service Quality on Customer Loyalty at NU Mart Minimarket, Pekalongan District - Fatmawati, Rizky; Ariyanti, Rizka; Imron, Ali (LP3M Universitas Putra Bangsa, 2025)
At the NU Mart Minimarket in the Pekalongan Barat District, this study attempts to test, examine, and elucidate the effects of brand trust, brand awareness, discount, and service quality on customer loyalty. This study falls under the category of quantitative research. 100 consumers of the NU Mart minimarket in the Pekalongan Barat District were given a questionnaire to complete. SPSS Statistics 20.0 was utilized for data processing. use purposive sample in conjunction with non-probability sampling. Analysis of multiple linear regression is used in this study. The study's findings indicate that while service quality (tcount 3.434), discount (tcount 3.127), and brand trust (tcount 4.954) all partially affect customer loyalty (Y), brand awareness (tcount 0.820) has no effect on customer loyalty because tcount > (ttable 1.9852). Simultaneously Brand Trust, Brand Awareness, Discount and Service Quality together influence Customer Loyalty with tcount 71329 > tcount 2.46.